An Appropriate Model for Talent Management Based On Emotional, Organizational and Cultural Intelligences - Shayanipour, Zahra; Imani, Mohammad Naqi; Karimzadeh, Samad (Iranian Journal of Educational Sociology, 2022)
Abstract Purpose: The aim of this paper was to provide a talent management model based on emotional, organizational and cultural intelligence in Islamic Azad Universities, Fars province. Methodology: The research used descriptive and survey methods and the statistical population included all faculty members of Islamic Azad University, Fars Province in educational year in 2016-2017. The sample size included 332 subjects who were selected by stratified random sampling method. The data collection tools were talent management questionnaire (2007), Albrecht organizational intelligence questionnaire (2003), Goleman emotional intelligence questionnaire (2000) and Ang and Earley cultural intelligence (2004). Findings: Data were analyzed using the SPSS and Amos software. Pearson correlation results showed that there is a significant positive relationship between emotional intelligence and its components with talent management. There is also a significant positive relationship between organizational intelligence and its components with talent management, as well as there is a significant positive relationship between cultural intelligence and its components with talent management. Structural equation modeling results showed that emotional intelligence variable (0.24%) explained the highest cultural intelligence variance. Conclusion: Therefore, the results of the study suggest that by increasing emotional, organizational and cultural intelligence among the faculty members of Azad University, talent management will be also improved